Predictive influences of using ict in relation to use behavior of youth entrepreneurship intention - Parvin, Ali (2020)
The maze around Information and Communications Technology (ICT) has led youth to narrow their focus on technologies that are beneficial for venturing into entrepreneurial activities. Internet in particular, offers countless of opportunities that one with efficient skills could attain with promising benefit of brighter career possibilities and income expansions. In Malaysia, youth find opportunities in self-employment through internetbased platforms and by far it is the best way to curb unemployment status. Yet, to some degree, this requires technical or rather internet skill competency which most of youth at young age find it challenging. The purpose of this study is to examine internet usage towards entrepreneurship intention among youth in Malaysia. The study used quantitative approach whereby 400 youths in Klang Valley, Malaysia were selected as respondents. The population in this study comprises of Malaysians from three major different groups namely Malay, Chinese and Indian. This study is based on nonprobability sampling. Data were gathered using convenience sample through selfadministrative questionnaire, which were written in English and Bahasa Melayu. The statistical data processed through two parts, which are descriptive statistic analysis and inferential statistic analysis. For descriptive data analysis, percentage, mean and standard deviation were used to understand how youth are utilizing internet for entrepreneurial activities. Likewise, for inferential statistic, the Pearson Correlation, Regression, t-Test and ANOVA were conducted to identify the relationship between predictive variables and use behavior of youth entrepreneurship intention. The findings of Pearson Correlation indicated there is a relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, internet knowledge and internet skill competency towards use behavior of youth entrepreneurship intention. In depth analysis of regression test had shed a light on variables that contributed significantly to dependent variables. The result indicated that youth who have facilitating condition, social influence as well as internet knowledge have high levels of use behavior of entrepreneurship intention. On the other hand, the analysis of t-Test and ANOVA reveals there is no significant relationship between gender (male and female) with use behavior of youth entrepreneurship intention. Contrary, there is a significant relationship between age and use behavior of youth entrepreneurship intention. In short, youth should accept and practice certain elements such as access to right information, competency in using the internet and acquiring technical skills in order to strengthen their entrepreneurial engagement. This study stresses on the need for youth to advocate and utilize internet resources for one-self as it will lead them into an elite society where successful entrepreneurial measures are guaranteed among generations of internet users.